DEVELOPMENT OF METHODS FOR IMPROVING THE EFFICIENCY OF NATURAL GRAPHITE CHEMICAL PURIFICATION - МАКЄЄВА, І. С.; КИСЛОВА, О. В.; ПАТЛУН, Д. В.; ХОМЕНКО, В. Г.; НІКУЛІН, Д. О. (Technologies and Engineering, 2024)
Purpose. This study aims to analyze the efficiency of chemical purification processes for natural graphite samples using mineral acids and their mixtures with the ammonium fluoride. Methodology. Purification of natural graphite samples was performed by their treatment with nitric and sulfuric acid solutions, supplemented with ammonium fluoride. The degree of graphite purification was assessed through the method of ashing the mass in a muffle furnace until a constant weight was achieved at 1050 ºC. The chemical composition of the impurities within the graphite samples was identified by X-ray fluorescence analysis using the Oxford Instruments X-Supreme 8000 spectrometer (United Kingdom). Findings. A variety of chemical purification methods for graphite materials, specifically for the GAK-2 and GUPG-92 brands, were evaluated utilizing mineral acids of diverse compositions. The graphite samples underwent analysis both before and after the chemical purification process. The investigation revealed that the proposed method of purification with H2SO4+NH4F solution successfully achieved graphite purity levels of 99.97% for GAK-2 in single-stage method and 99.44% for GUPG-92 in two processing stages. Originality. The efficacy of the proposed method for acid treatment, particularly in the presence of an ammonium fluoride additive for the purification of selected samples, was confirmed by the X-ray fluorescence and gravimetric analysis. Notably, this study marks the first instance of employing diluted acid solutions for the effective purification of graphite. Practical value. The production of chemically purified graphite holds significant relevance for advancing the technological processes involved in the industrial manufacture of raw materials essential for lithium-ion batteries and innovative materials such as graphene. The formulation and enhancement of effective chemical purification methods are instrumental in diminishing the costs associated with procuring graphite of high purity.